2006
DOI: 10.1590/s0102-33062006000200015
|View full text |Cite
|
Sign up to set email alerts
|

Florivory and sex ratio in Annona dioica St. Hil. (Annonaceae) in the Pantanal at Nhecolândia, southwestern Brazil

Abstract: RESUMO -(Florivoria e Razão Sexual em Annona dioica St. Hil. (Annonaceae) no Pantanal da Nhecolândia, Brazil). Annona dioica é uma espécie arbustiva de até dois metros de altura, amplamente distribuída nos cerrados. Esta espécie é conhecida por oferecer muitas flores, mas produzir poucos frutos. Enquadra-se como androdióica, possuindo indivíduos machos e hermafroditas na população. O objetivo deste estudo foi registrar a razão sexual e comparar a taxa de florivoria entre flores masculinas e hermafroditas. A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Our results indicated that corolla was the most attacked flower part by florivores (96% of the cases), followed by reproductive organs (34%) and calyx (17%). In a previous study in the Pantanal, damage caused by florivorous beetles was also greater on the petals than on the reproductive organs of Annona dioica (58% vs. 42%, respectively; Neto and Teixeira 2006). In a temperate forest in Central Mexico, florivores preferentially attacked corollas (69%) of Solanum rostratum (Vega‐Polanco et al, 2020).…”
Section: Discussionmentioning
confidence: 66%
“…Our results indicated that corolla was the most attacked flower part by florivores (96% of the cases), followed by reproductive organs (34%) and calyx (17%). In a previous study in the Pantanal, damage caused by florivorous beetles was also greater on the petals than on the reproductive organs of Annona dioica (58% vs. 42%, respectively; Neto and Teixeira 2006). In a temperate forest in Central Mexico, florivores preferentially attacked corollas (69%) of Solanum rostratum (Vega‐Polanco et al, 2020).…”
Section: Discussionmentioning
confidence: 66%
“…Although there is variation in the incidence and intensity of florivory between environments and between terrestrial and aquatic species, no studies have evaluated these variables considering plant species with female and male flowers (dioecious or monoecious). Most studies have focused on species that have hermaphroditic flowers [ 2 ], and a few studies on gynodioecious species or plants with flowers of separate sexes (dioecious or monoecious) [ 6 , 9 , 40 ]. This suggests that future studies should focus on plant species with other sexual expressions, allowing us to identify patterns and differences among them.…”
Section: Discussionmentioning
confidence: 99%